2014
DOI: 10.1002/acp.3006
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements Indicate the Temporal Organisation of Information Processing in Graph Comprehension

Abstract: Hierarchical graphs (e.g. file system browsers and preference trees) represent objects (e.g. files and folders) as graph nodes and relations between them (e.g. sub-folder relations) as lines. We investigated the temporal organisation of two processes that are necessary for comprehending such graphs-search for the graph nodes and reasoning about their relation. We tracked eye movements to change graphs while participants interpreted them. In Experiment 1, we masked the graph at a time when search processes had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A more focused pattern could be simply QC-IL-MC, and a less sure pattern would look like QC-IL-QC-IL-MC-QC-MC. Although it is difficult to identify when exactly a participant transitioned from one step to the next-or whether some parallel processing occurred at transitions or on a broader scale, despite studies that have shown the dominance of serial over parallel information processing (Körner, 2011;Körner, Höfler, Tröbinger, & Gilchrist, 2014)-the scheme above is expected to capture the major steps of the problem-solving process.…”
Section: Discussionmentioning
confidence: 99%
“…A more focused pattern could be simply QC-IL-MC, and a less sure pattern would look like QC-IL-QC-IL-MC-QC-MC. Although it is difficult to identify when exactly a participant transitioned from one step to the next-or whether some parallel processing occurred at transitions or on a broader scale, despite studies that have shown the dominance of serial over parallel information processing (Körner, 2011;Körner, Höfler, Tröbinger, & Gilchrist, 2014)-the scheme above is expected to capture the major steps of the problem-solving process.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting next step would be to employ eye tracking methodologies [34,38] to provide an interesting new perspective on questions relating to the utility of animation, small multiples and drawing stability. Such studies may help illustrate the root causes of the effects that we have measured with previous experiments.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Note that we did not find effects of compatibility on error rates, except for the marginally significant interaction in the initial performance analysis of Experiment 1. Although error rate is a well-established and sensitive measure used in the study of graph comprehension processes (e.g., Körner, Höfler, Tröbinger, & Gilchrist, 2014;Meyer, 2000), it is possible that our setting, which did not impose any time limit for responding, together with the instruction to respond accurately, contributed to the selective effects on RTs. However, one should keep in mind that many real-life situations (e.g., attending a research presentation) provide graphs for only a limited amount of time; thus, in these situations one would expect more comprehension errors for incompatible panels.…”
Section: Discussionmentioning
confidence: 99%